Cooperation and Conflict: Mothers and Daughters’ Negotiation over Sexual Conduct in Morocco - Yamani, Ahmed Kadiri Hassani (European Scientific Journal, ESJ, 2020)
Drawing on capabilities approach and the framework of the family as a system of cooperative conflicts (Sen, 1990), the present study explores how interaction between parents and their adolescent daughters shapes girls’ agency in negotiating decision about their sexual conduct. Four areas of negotiation are examined: wearing hijab, importance of virginity until marriage, opposite-sex friendships, and dating. This study explores how communication and sexuality of Moroccan girls is mediated through their mothers and socialization. Separate group discussions and individual in-depth interviews were conducted with 76 Moroccan mothers and 93 daughters (age range 14-20) in Rabat city. Analysis revealed that negotiations for a particular group in each area were rarely characterized by conflict, and more often than not by mutual agreement. A firm grasps of religion, a clear understanding of duties and obligations in the family, as well as daughters’ need to balance family demands and socialization with peers plays a significant role on daughters’ agency in negotiating decisions about wearing hijab, virginity until marriage, opposite-sex friendships, dating and marriage. Findings showed that little communication regarding sexuality as a private experience happened between mothers and daughters. This was also confined primarily to the risks of premarital sexual relationships to the social order.